Caregiver Burden on Caregiver with Chronic Disease - Novita Nirmalasari; Ike Wuri Winahyu Sari (Journal Of Nursing Practice, 2025)
Background: The prevalence of chronic diseases in Indonesia increases every year with various accompanying physical and psychological problems. In this state, patients require the assistance of their families as caregivers. Family caregivers are an important source of care for patients which faced physical, psychological, social, and economic challenges when providing care. Purpose: The purpose of this study was to identify the burden among family caregivers of chronic diseases patients. Methods: This cross-sectional study was conducted from April 2021 to November 2021 in the Hospital and Community Health Center. Purposive sampling was used to determine the inclusion and exclusion criteria for the 180 respondents in this study. The Caregiver Reaction Assessment-Indonesian Version (CRA-ID) was used to measure their burden. Data were analyzed using descriptive and bivariate analyses with independent t-tests and Pearson correlation. Results: The results of the research showed a significant relationship between caregiver burden and age (p-value=0.000), but no relationship was found between gender, marital status, relationship with patients, caregiver education, caregiver job, and income with each p-value 0.756; 0.725; 0.791; 1.000; 0.354 and 0.301. Conclusion: Age was significantly related to caregiver burden in caring for family members who suffered from chronic diseases. Health services were expected to provide adequate information for caregivers about caring for chronic disease patients to reduce caregiver burden.